DEMYSTIFYING TOXIC RELATIONSHIPS: DATING DYNAMICS OF ENFORCED SLAVERY AND THE PARADOXICAL TERM "SURVIVING" - Venesa Carolina; Nacha Enjelika; Septia Monica; Weni Prinata; Lamiang; Yeremia; Yola Pradita (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
The objective of this research is to find the space of experience (level of depression, relationship disharmony, resilience, and rising from bad experiences), the subject's narrative as an actor of dating as the victim and explore the extent of the losses obtained when entering the realm of toxic relationships. The problem of this study is that researchers find overlapping complexities of experience as experiences that cannot be quantified by numbers that need to be parsed one by one through the narratives of the three research subjects Wkhcath, Ldckyga, and Skcapthcu who are currently undergoing the lecture process on one of the campuses in Central Kalimantan. The research method is qualitative research with data search techniques through a series of interviews with three research subjects from Central Kalimantan (including the boyfriends of the three research subjects). Researchers before the interview asked permission first before recording the conversation and then the recording results were transferred into writing. The results showed that the problems of the three female students did not always originate during the lecture process, but had been present since they were in high school. In addition, the research results from the three research subjects show that resilience and daring to take a stand when experiencing oppression are important as an attitude of autonomy as well as a space of respect that should not be used as property